FAKTOR GEOGRAFIS YANG MEMPENGARUHI PRODUKSI TANAMAN TEH PT. MITRA KERINCI KABUPATEN SOLOK SELATAN - puput bella mulbes; Ratna Wilis (DEPARTEMEN GEOGRAFI FIS UNP, 2022)
ABSTRACT This study aims to determine the effect of rainfall, soil type and slope on the production of tea plants and determine the marketing of PT. Mitra Kerinci, South Solok Regency. The method used in this research is descriptive quantitative. The data analysis technique used is simple regression analysis and overlay method. The results showed that 1) Rainfall had no significant effect on tea plant production. The simple regression analysis model obtained is Y = 13864.282 + 0.743X, indicating that each increase in rainfall of 1 mm / year, there will be an increase in tea plant production by 0.743 tons. 2) The overlay results show that the type of soil and the slope of the slope affect the production of tea plants. The highest tea production has Andosol soil type with a slope of 8-15%, while the lowest has a Podsolic soil type with a slope of 0-8%. 3) Tea marketing of PT. Mitra Kerinci has spread across the islands of Java and Sumatra, with consumers mostly tea companies.